A review of sheep and goats in Eastern Africa - Kiwuwa, G.H. (1983)
Indigenous sheep and goats contribute substantial wool, milk, meat and skin to the regional economy. This review identifies a number of breeds/types of sheep and goats and their principal uses in eastern Africa. Their production and reproduction traits are summarised and various indices of productivity indicated. For the purposes of species comparison, performance characteristics for three indigenous breed of sheep (Red Masai, Blackhead Persian and Sudan-riverine) and four indigenous breeds of goats (Galla, Mubende, Small East African and Sudan-Nubian were considered. The sheep tended to be 36 per cent more efficient biologically than goats. The difference was largely reflected in higher weaning weight (19.28 kg) for sheep as compared to weaning weight of 9.40 kg for goats. The annual net returns per animal unit (A.U.) or per female breeder revealed that raising goats for meat and fibre (mohair) could be 230 per cent more profitable than raising for meat and wool. The best breeds of sheep identified were Sudan-riverine, the Blackhead Persian and the Dorper; while the Mubende, the Galla and the Sudan Nubian goats were promising for future genetic improvement programmes.